Partially Hydrolyzed Whey Protein: A Review of Current Evidence, Implementation, and Further Directions - Badriul Hegar; Zakiudin Munasir; Ahmad Suryawan; I gusti Lanang Sidhiarta; Ketut Dewi Kumara Wati; Erfi Prafiantini; Irene Irene; Yvan Vandenplas (World Nutrition Journal, 2021)
Background: Human milk is known to be the best nutrition for infants as it provides many health benefits. For non-breastfed infants, cow's milk based infant formula is the most optimal option to provide the needed nutrition. However, approximately 2-5% of all formula-fed infants experience cowâ€™s milk allergy during their first year of life. Partially hydrolyzed whey formula (pHF-W) have been widely recommended to prevent the development of allergic disease in infants. However, according to epidemiological data, approximately half of the infants developing allergy are not part of the at-risk group.Objectives and Methods: This article aims to review the effects of pHF-W in preventing allergy, especially atopic disease, in all non-breastfed infants, as well as the safety aspect of pHF-W if used as routine formula. The role of pHF-W in the management of functional gastro-intestinal (GI) disorders is also reviewed.Results: Several clinical studies showed that pHF-W decrease the number of infants with eczema. The strongest evidence is provided by the 15-year follow up of the German Infant Nutritional Intervention study which showed reduction in the cumulative incidence of eczema and allergic rhinitis in pHF-W (OR 0.75, 95% CI 0.59-0.96 for eczema; OR 0.67, 95% CI 0.47-0.95 for allergic rhinitis) and casein extensively hydrolysed formulaÂ  group (OR 0.60, 95% CI 0.46-0.77 for eczema; OR 0.59, 95% CI 0.41-0.84 for allergic rhinitis), compared to CMF as a control, after 15 years of follow-up. pHF-W was also found to be beneficial in the management of functional GI disorders such as regurgitation, constipation and colic.Conclusions: The use of pHF-W in allergic infants has been recommended in various guidelines across the countries, as a primary prevention of allergic disease. One pHF-W has been approved by the US FDA and the European Commission's European Food Safety Authority (EFSA) for its safety and suitability as a routine infant formula for all healthy infants. According to the data obtained in the management of functional GI disorders, pHF-W is better tolerated than formula with intact protein. Further studies assessing the effect of routine use of pHF-W in a larger population of non-breastfed infants should also be conducted, in order to observe any potential harm and to determine the benefit and cost-effectiveness ratio.